Aplicação de plasma atmosférico em descarga por barreira dielétrica para descontaminação de água de coco - Fernandes, Magda Jordana (Universidade Federal Rural do Semi-Árido, 2020)
Due to the increasing consumption of coconut water in plastic packaging, and the risk of microbial contamination, there is a concern to use decontamination steps of the coconut water during the industrial process. Knowing the limitations and disadvantages of conventional thermal processes, atmospheric plasma technology has been widely studied as an alternative process for solid or liquid food decontamination. Thus, in the present work, the efficiency of atmospheric plasma in coconut water decontamination was studied, in a surface dielectric barrier discharge configuration, using atmospheric air as the working gas, at a voltage of 10.3 kV and frequency of 4 kHz. Standard strains of Escherichia coli and Candida albicans were inoculated in coconut water and treated with times of 7.5 min, 15 min and 22.5 min, to test their inactivation. The concentrations of nitrite and nitrate, sodium and potassium, variations in pH, electrical conductivity, total soluble sugars, reducing sugars and total soluble solids were also analyzed. It was observed that, for the time of 22.5 min, E. coli had inactivation of 100%, and C. albicans of 90.3%. Optical emission spectroscopy indicated a strong presence of reactive nitrogen and oxygen species in the UV range (300 to 400 nm), which contributes to the inactivation of microorganisms. Minimal physical-chemical variations were observed in the plasma treated samples, which is positive for the consumption of the drink. These results demonstrate a potential path for the development of extremely effective cold plasma treatments to preserve liquid food in general, requiring logistics for large-scale application.
Keywords: Plasma frio; Descontaminação de alimentos; Cocos nucifera L.; Inativação microbiana; Cold plasma; Food decontamination; Cocos nucifera L.; Microbial inactivation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA